PEACE AGREEMENT, AS A METHOD OF RESOLUTION ECONOMIC DISPUTES - Slobodska, Iryna; Sohar, Vladislava (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: an essential feature of a truly democratic legal state is the focus on the peaceful resolution of legal conflicts, which is why our country has developed a whole system of conciliation procedures, both extrajudicial and judicial in nature (clear examples of the latter are amicable agreements and settlement of disputes with the participation of a judge). But it is worth noting that the effectiveness of the application of these procedures directly depends on the presence of clear mechanisms for the implementation of legislative guarantees of the fulfillment of the terms of the settlement agreement in case of non-fulfilment of it voluntarily. That is why the specified scientific publication is aimed at analyzing the features of the settlement agreement and modern judicial practice regarding its conclusion during the consideration of cases in commercial courts, identifying problems of application and proposing possible solutions. Research methods: this scientific work was written by the authors using generally recognized methods of scientific knowledge, such as formal, comparative-legal, analytical, systemic-structural and others. Results: settlement agreements in business practice are an important means of dispute resolution, which reflects not only speed and efficiency in resolving conflicts, but also flexibility in defining conditions, preserving business relations, and reducing costs. The results of the research presented in this scientific article make it possible to determine further steps to eliminate the problems of the application of peace agreements in Ukraine. They allow the parties to avoid complex and lengthy court procedures, focus on joint search for a solution, and also ensure protection of confidentiality and commercial information. However, it is important to remember the possible risks, such as non-fulfillment of the terms of the agreement, as well as restrictions that may arise in the process of concluding and executing the agreement. Thus, settlement agreements remain a key tool for achieving mutually beneficial solutions in business matters, contributing to the sustainable development of business and partnership relations. Discussion: the discussion in this study is devoted to the analysis of the role of settlement agreements in the context of Ukrainian legislation and practice, namely the resolution of economic disputes through settlement agreements in the conditions of the Ukrainian business environment.